Asia's infrastructure challenges: Issues of institutional capacity - Susan F. Stone (Asian Development Bank Institute (ADBI), 2008)
The Asian region has experienced substantial growth over the past several decades. Indeed, a quarter of all world exports now come from East Asia. Strong infrastructure underpinnings have often been cited as a major factor contributing to this success, and an important competitive advantage over other developing regions (Kuroda et al. 2006). However, a decline in spending over the past 10 years has raised concerns that this infrastructurederived competitive advantage is eroding. Overall quantity and quality of infrastructure services remain uneven both across, and within, countries in the Asian region. Strong investment in infrastructure is needed to support continuing efforts to achieve overall growth as well as poverty reduction.
Keywords: H54; E02; 330